2016
DOI: 10.1038/mp.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome 16p13.11 microduplication causes hyperactivity through dysregulation of miR-484/protocadherin-19 signaling

Abstract: Chromosome 16p13.11 microduplication is a risk factor associated with various neurodevelopmental disorders such as attention-deficit/hyperactivity disorder, intellectual disabilities, developmental delay and autistic spectrum disorder. The underlying molecular mechanism of this genetic variation remained unknown, but its core genetic locus—conserved across mice and humans—contains seven genes. Here, we generated bacterial artificial chromosome-transgenic mice carrying a human 16p13.11 locus, and these mice sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 45 publications
5
54
0
Order By: Relevance
“…In silico analysis identified the Pcdh19 3′UTR as a target for miR-484, and luciferase assays confirmed that miR-484 downregulates Pcdh19. Knockdown of Pcdh19 by shRNA delivered via in utero electroporation led to increased differentiation of radial glia into basal progenitors, consistent with Pcdh19 downregulation being the mechanism by which miR-484 acts [162]. Though it is not yet clear the extent to which Pcdh19 contributes to the various defects in 16p13.11 microduplication syndrome, its implication in this disorder further strengthens its link to neurological disease.…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 76%
See 2 more Smart Citations
“…In silico analysis identified the Pcdh19 3′UTR as a target for miR-484, and luciferase assays confirmed that miR-484 downregulates Pcdh19. Knockdown of Pcdh19 by shRNA delivered via in utero electroporation led to increased differentiation of radial glia into basal progenitors, consistent with Pcdh19 downregulation being the mechanism by which miR-484 acts [162]. Though it is not yet clear the extent to which Pcdh19 contributes to the various defects in 16p13.11 microduplication syndrome, its implication in this disorder further strengthens its link to neurological disease.…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 76%
“…Finally, Pcdhs have been implicated in neuropsychiatric disorders including ASD, intellectual disabilities, and attention deficit hyperactivity disorder (ADHD) resulting from a duplication of the 16p13.11 locus, which contains 7 genes [162]. Fujitani et al [162] present evidence that a microRNA, miR-484, is the gene responsible for the behavioral phenotypes modeled in mice.…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been obtained in the zebrafish, where loss of the δ2-Pcdh, pcdh19 , increases proliferation and the number of pcdh19 -expressing neurons in the optic tectum (Cooper et al 2015). The micro-RNA, miR-484, affects neurogenesis by regulating pcdh19 expression (Fujitani et al 2016). Increased levels of miR-484 cause hyperactivity in mice, which could be related to neurodevelopmental disorders associated with microduplications of this locus in humans.…”
Section: Neurogenesis and Neuronal Migrationmentioning
confidence: 99%
“…[25][26][27] Indeed, premature neurogenesis has been associated to gross brain abnormalities in a thalassemia/mental retardation syndrome X-linked (ATRX), consistently with the microcephaly observed in patients affected by this disorder. 28,29 Similarly, accelerated cell cycle and overproduction of GABAergic inhibitory neurons were described in iPSC-derived brain organoids of Autism Spectrum Disorder (ASD) patients characterized by macrocephalia.…”
mentioning
confidence: 90%